Screening and Identification of Therapeutic Targets for Pulmonary Arterial Hypertension Through Microarray Technology - Li, Qing; Meng, LingBing; Liu, DePing (Frontiers in Genetics, 2020)
Pulmonary arterial hypertension (PAH) is a rare but fatal disease characterized by vascular cell proliferation; the pathogenesis of PAH has yet to be fully elucidated. Publicly available genetic data were downloaded from the Gene Expression Omnibus (GEO) database, and gene set enrichment analysis (GSEA) was used to determine significant differences in gene expression between tissues with PAH and healthy lung tissues. Differentially expressed genes (DEGs) were identified using the online tool, GEO2R, and functional annotation of DEGs was performed using Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. Next, the construction and module analysis of the protein-protein interaction (PPI) network and verification of the expression level of hub genes was performed. Finally, prediction and enrichment analysis of microRNAs associated with the hub genes was carried out. A total of 110 DEGs were detected by screening PAH and healthy lung samples. The expression of nine genes [polo-like kinase 4 (PLK4), centromere protein U, kinesin family member 20B, structural maintenance of chromosome 2 (SMC2), abnormal spindle microtubule assembly, Fanconi Anemia complementation group I, kinesin family member 18A, spindle apparatus coiled-coil protein 1, and MIS18 binding protein 1] was elevated in PAH; this was statistically significant compared with their expression in healthy lung tissue, and they were identified as hub genes. GO and KEGG analysis showed that the variations in DEGs were abundant in sister chromatid cohesion, mitotic nuclear division, positive regulation of cell division, cell proliferation, the nucleus, and regulation of the actin cytoskeleton. In conclusion, this study has successfully identified hub genes and key pathways of PAH, with a total of 110 DEGs and nine hub genes related to PAH, especially the PLK4 and SMC2 genes, thus providing important clues for the in-depth understanding of the molecular mechanism of PAH and providing potential therapeutic targets.